UV-induced reactive oxygen species and transcriptional control of 3-deoxyanthocyanidin biosynthesis in black sorghum pericarp - Schumaker, Brooklyn; Mortensen, Lauren; Klein, Robert R.; Mandal, Sabyasachi; Dykes, Linda; Gladman, Nicholas; Rooney, William L.; Burson, Byron; Klein, Patricia E. (Frontiers in Plant Science, 2024)
Black pericarp sorghum has notable value due to the biosynthesis of 3-deoxyanthocyanidins (3-DOAs), a rare class of bioactive polyphenols valued as antioxidant food additives and as bioactive compounds with cytotoxicity to human cancer cells. In this study, a metabolic and transcriptomic study was conducted to ascertain the cellular events leading to the activation of 3-DOA biosynthesis in black sorghum pericarp. Prolonged exposure of pericarp during grain maturation to high-fluence ultraviolet (UV) light resulted in elevated levels of reactive oxygen species (ROS) and the activation of 3-DOA biosynthesis in pericarp tissues. Associated with 3-DOA biosynthesis was the transcriptional activation of specific family members of early and late flavonoid biosynthesis pathway genes. A working model of UV-induced 3-DOA biosynthesis in black pericarp is proposed that shares features of plant immunity associated with pathogen attack or mechanical wounding. The present model depicts ROS biosynthesis, the transcriptional activation of receptor kinases and transcription factors (TFs) including NAC, WRKY, bHLH, AP2, and C2H2 Zinc finger domain. Associated with these cellular events was the downstream activation of defense-related pathways and the biosynthesis of secondary metabolites including 3-DOAs. Promoter analysis of genes highly correlated with 3-DOA biosynthesis in black pericarp were enriched in MYB and HHO5/ARR-B motifs. Light microscopy studies of black pericarp tissues suggest that 3-DOAs are predominantly localized in the epicarp and are associated with the cell wall.